A study of nodule detection using Opaque Object Filter - Wong, L. P.; Ewe, H. T. (2006)
This paper describes a study of Opaque Object Filter to extract region with nodule from chest x-ray image. A gray level chest x-ray image is preprocessed using Euler number algorithm to extract lung region. Defined Euler number algorithm is a statistical extraction of data obtained from Euler numbers for binary image. Suitable threshold value is computed based on minimum and maximum of the correlated gray scale value. After lung region was extracted, we applied our defined Opaque Object Filter to extract nodules image window. We use defined filter to perform heuristic search through the chest x-ray image. Defined Opaque Object Filter utilized radius and spatial axis vector analysis to extract nodules image window. Noise filter is defined to eliminate the border of lung area effects. A flow chart for the search is introduced. Initial result shows the filter is able to extract nodules image window within chest x-ray image.